Phronetic Planning’s Janus Face: Charting Elite Advantage in Tehran’s Land Use Decisions - Max Stephenson; Mohammadmehdi Panahi; Neda Moayerian (Land)
This study employed a phronetic (practical wisdom) analytic framework to explore the Tehran, Iran, City Council’s Article 5 Commission’s land use decisions from 1999 to 2024. We argue that, during that period, the Commission nominally embraced practical wisdom in lieu of episteme or techne as the arbiter of its choice making. Nonetheless, during those years, its members disproportionately granted land use change permits to the Tehran Comprehensive Plan that principally benefited members of the city’s upper class. Our central finding underscores the Commission’s role in advancing elite rather than broader public interest needs. We conclude that even a nominally phronetic planning process can fall prey to willfully undemocratic choice making. In this case, this occurred when the discretionary powers delegated to the Commission to serve the broader public interest were instead employed routinely to serve the interests of an elite. Our analysis highlights the urgent need for more ethical, popularly accountable, and equitable planning practices to serve the general population of Tehran.